Connections : - Alesso, H. P. (Wiley-Interscience, 2008)
In a collection of compelling chapters, this book shows how the past flows into the future: Starting with the inspirational journey of two young inventors creating Google, the world's best search engine, it identifies the stepping stones toward `perfect search.'The growth of the Information Superhighway links succeeding proof of principle inventions fueling Moore's Law: the vacuum tune, the transistor, and the microprocessor, thereby illuminating the next generation of chips. The incubator research center of Xerox PARC led the breakthrough in six technologies, only to fail commercially, in contrast to the success of Apple and IBM PC. - setting the stage for innovative breakthroughs in small devices.